2021
DOI: 10.1186/s12870-021-03329-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of the AP2/ERF gene family in ginger: evolution and expression profiling during development and abiotic stresses

Abstract: Background AP2/ERF transcription factors (TFs) constitute one of the largest TF families in plants, which play crucial roles in plant metabolism, growth, and development as well as biotic and abiotic stresses responses. Although the AP2/ERF family has been thoroughly identified in many plant species and several AP2/ERF TFs have been functionally characterized, little is known about this family in ginger (Zingiber officinale Roscoe), an important affinal drug and diet vegetable. Recent completio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 93 publications
6
22
0
1
Order By: Relevance
“…AtDDF2 most abundantly expressed in rosette leaves and stems, conversely, AeAP2/ERF081 did not express, which suggested that the functions gradually appeared divergence during evolution. The similar pattern was found in ginger ( Zingiber officinale ) [ 53 ]. Additionally, partial genes have high transcription abundance.…”
Section: Discussionsupporting
confidence: 79%
“…AtDDF2 most abundantly expressed in rosette leaves and stems, conversely, AeAP2/ERF081 did not express, which suggested that the functions gradually appeared divergence during evolution. The similar pattern was found in ginger ( Zingiber officinale ) [ 53 ]. Additionally, partial genes have high transcription abundance.…”
Section: Discussionsupporting
confidence: 79%
“…The reason for this phenomenon may be due to the ftsH gene duplication or gene loss during the evolution of the tobacco plant, resulting in the absence of the ftsH gene on some chromosomes and the appearance of multiple genes on others. In addition, the frequency of gene occurrence was not related to chromosome length and gene density [26].…”
Section: Chromosomal Location Of Ntftsh Gene and Gene Segment Duplica...mentioning
confidence: 79%
“…From tobacco's whole genome sequence data, we identified 20 members of the ftsH gene family (Additional file 1: Table S1). The genes were renamed according to their order and position on the chromosome, from NtftsH1 to NtftsH20 [26]. At the same time, the physicochemical properties and subcellular localization of gene sequences were analyzed.…”
Section: Identification Of Tobacco Ftsh Genementioning
confidence: 99%
“…Members of the AP2/ERF family have been identified and scaled in many species, including 146 in Arabidopsis thaliana [ 11 ], 163 in Oryza sativa [ 11 ], 134 in Fagopyum Tataricum [ 14 ], 364 in Salix matsudana [ 15 ], 163 in Zingiber officinale [ 16 ], 322 in Triticum aestivum [ 17 ], 189 in Panax ginseng [ 18 ] and 531 in Brassica campestris [ 19 ]. AP2/ERF transcription factor family has been confirmed to be involved in a variety of abiotic stress responses; for example, AtCBF1/2/3 control low temperature responses in Arabidopsis [ 20 , 21 ], ZmDREB2a participates in heat response in maize [ 22 ], and GmERF4/7 mediate salt stress response in soybean [ 23 ].…”
Section: Introductionmentioning
confidence: 99%